The Concept of Originality in Art and its Determinants in the Creative Experience in the Contemporary - Valadares Souza, Geruza (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
We propose to investigate the concepts of po.esis , t.chne , al.theia and praxis and their relationship with human creation in three historical periods: in Greek antiquity, in modernity and in contemporary times, in order to answer the question: What is the state of creation in the contemporary? In this sense, the research analyzes the concept of originality in antiquity and modernity, with the aim of demonstrating the determining influence of this concept on the understanding of artistic experience in the contemporary world.